L’homo errans nell’era dell’infallibilità tecnica (Altre Modernità, 2017)
In this paper the phenomenon of human error will be described in relationship to human performance in complex high-technology systems. Misconceptions could lie behind the terms “human error” at several levels: cognitive, emotional, moral, and cultural. From the cognitive perspective, human error has been widely investigated and proper theoretical models can accurately describe its nature and functions. From the emotional perspective, making a mistake could lead to feelings such as guilt and shame, which could have relevant effects on how people cope with the situation and try to remedy the error. Concerning the moral perspective on human error, we describe a dangerous mix of cognitive biases and the judgment of the person. The cognitive biases frame the mistake as something that was predictable and avoidable, and the severity of the blame is correlated with the gravity of the outcomes. These distortions critically move the perspective from an analysis of behavior to moral judgment of the person, a typical effect of the so called “blame culture”. Finally, from the cultural perspective, human behavior is superficially compared to the reliability of technology. Blaming humans for not being like machines is just a symptom of current technology-centered culture. Given the complexity of today’s socio-technical systems, the challenge is to harmonize human and automation characteristics. The goal is not to make humans less prone to errors, but to make complex systems safer.